Plastic Surgery Medical Tourism in Colombia: A Review of 658 International Patients and 1,796 Cosmetic Surgery Procedures - Christopher Alexander Campbell, MD; Carolina Restrepo, MD; Genesis Navas, MD; Ileyna Vergara, MD; Laura Peluffo (Plastic and Reconstructive Surgery, Global Open, 2019)
Background:. Cosmetic surgery is at the forefront of a $60 billion medical tourism industry. Patients are now able to research options globally through the internet, and increasing numbers are seeking improved service, quality, and value through surgery overseas. This study examines 658 consecutive patients receiving 1,796 cosmetic surgery procedures at a private plastic surgery practice in Cartagena, Colombia. Methods:. We retrospectively reviewed the medical records of 658 consecutive international patients receiving cosmetic surgery at a private plastic surgery practice in Cartagena, Colombia. Results:. Patients traveled to Colombia from 34 different countries spread across 6 continents. Ninety percent of patients came from North America. Patients from the United States represented 38 states and the District of Columbia, and Canadian patients represented 7 provinces. Eighty-three percent of patients were women and 90% were between the age of 20 and 54. The 658 patients in this study had a total of 1,796 cosmetic surgery procedures, involving 5,456 surgical sites. Seventy-two percent of patients received combination procedures with an average of 2.7 procedures per patient. Ninety-nine percent of cases were performed under general anesthesia and 100% were performed in an accredited hospital. Conclusions:. Our data highlight trends defining plastic surgery medical tourism. Our data indicate that traveling for surgery is widely appealing, with women and men from diverse backgrounds traveling to Colombia from all over the world for a variety of procedures.